Drought severity-duration-frequency analysis of hydrological drought based on copula theory - Kwak, Jaewon, author; Kim, Yeon Soo, author; Lee, Jong So, author; Kim, Hung Soo, author; Colorado State University, publisher (Colorado State University. Libraries, 2012)
Recently, in Korea, occurrences of floods and droughts have been increased due to the climate change and drought is a recurrent phenomenon. But, recurring prolonged droughts have caused consequences and diverse impacts on human system. Therefore, understanding drought characteristics is indispensable element in well-prepared drought management. This study aims to investigate the hydrological droughts of upstream of Namhan river in Korea. For modelling of the joint distribution of drought duration and drought severity, the copula method is used to construct the bivariate drought distribution and return period from the predetermined marginal distributions of drought duration and drought severity.
Hydrology days 2012
AGU hydrology days 2012
2012 annual AGU hydrology days was held at Colorado State University on March 21 - March 23, 2012.
Keywords: drought; joint probability analysis; SDF curve